2012
DOI: 10.1371/journal.pone.0048204
|View full text |Cite
|
Sign up to set email alerts
|

Luminal Localization of α-tubulin K40 Acetylation by Cryo-EM Analysis of Fab-Labeled Microtubules

Abstract: The αβ-tubulin subunits of microtubules can undergo a variety of evolutionarily-conserved post-translational modifications (PTMs) that provide functional specialization to subsets of cellular microtubules. Acetylation of α-tubulin residue Lysine-40 (K40) has been correlated with increased microtubule stability, intracellular transport, and ciliary assembly, yet a mechanistic understanding of how acetylation influences these events is lacking. Using the anti-acetylated tubulin antibody 6-11B-1 and electron cryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 47 publications
2
89
0
Order By: Relevance
“…40 Acetylation of the Lys40 residue in a-tubulin is a well-noted MT modification, and acetylated a-tubulin (Ac-tubulin) is enriched at interpolar and kinetochore MTs in mitotic cells. 24 In our research, we showed that depletion of EWSR1 reduced the level of MT acetylation but did not affect the levels of MT polyglutamylation and detyrosination in mitotic cells, indicating that EWSR1 has a specific role in the regulation of MT acetylation. Moreover, EWSR1 is distributed in the nucleus during interphase but is localized to spindle MTs during mitosis.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…40 Acetylation of the Lys40 residue in a-tubulin is a well-noted MT modification, and acetylated a-tubulin (Ac-tubulin) is enriched at interpolar and kinetochore MTs in mitotic cells. 24 In our research, we showed that depletion of EWSR1 reduced the level of MT acetylation but did not affect the levels of MT polyglutamylation and detyrosination in mitotic cells, indicating that EWSR1 has a specific role in the regulation of MT acetylation. Moreover, EWSR1 is distributed in the nucleus during interphase but is localized to spindle MTs during mitosis.…”
Section: Discussionmentioning
confidence: 52%
“…24 Thus, we examined the effects of EWSR1 on a-tubulin acetylation. As shown in Figure 5A, cells transfected with control vector or Myc-EWSR1 were synchronized in mitosis with thymidine-MG132 treatment.…”
Section: Knockdown Of Ewsr1 Decreases A-tubulin Acetylationmentioning
confidence: 99%
“…Acetylated microtubules are generally thought to be more stable than unmodified microtubules, but no direct evidence has shown that acetylation modification of microtubules directly influences tubulin polymerization or depolymerization kinetics in vitro (18). In addition, no clear differences in microtubule structure or tubulin conformation have been found between electron cryomicroscopy reconstructions of maximally deacetylated or acetylated microtubules (19), and the levels at which kinesin-1 binds to acetylated microtubules and deacetylated microtubules are similar (20,21). These findings require further investigation into the mechanism by which acetylation of ␣-tubulin enhances the fusion of IBs of HPIV3 via interaction with the N-P complex.…”
Section: Discussionmentioning
confidence: 99%
“…A consecutive change in MT conformation might therefore enhance motor recruitment to MTs (Dompierre et al, 2007;Hammond et al, 2009;Reed et al, 2006). Conversely, the role of tubulin acetylation upon molecular motor recruitment and function has been questioned in motility assays using tubulin acetylated in vitro (Soppina et al, 2012;Walter et al, 2012). These studies proposed that the recruitment of kinesin-1 to acetylated MTs and its velocity were not affected, but other tubulin modifications (de-tyrosination and polyglutamylation) could have masked the effect of acetylation.…”
Section: Autophagy and Microtubules 1075mentioning
confidence: 99%